Causes and Consequences of Delayed Diagnosis of Anorectal Malformation in Children in a Resource-Constrained Environment - Zarqoon, Nida; Azam, Zunaira; Jawaid, Bilal; Farooq, Hiba; Naseer, Muhammad Fahad; Naseer, Ishaa (Biological and Clinical Sciences Research Journal, 2025)
Delayed diagnosis of anorectal malformations (ARM) remains a frequent challenge in resource-constrained settings and is associated with increased neonatal morbidity and preventable complications. Evidence from low- and middle-income countries suggests that gaps in early neonatal examination and referral pathways contribute substantially to late presentation. Objective: To compare clinical presentation, early postoperative outcomes, and underlying causes of delayed diagnosis among neonates with anorectal malformations presenting to a tertiary care hospital in Pakistan. Methods: A cross-sectional comparative study was conducted at Holy Family Hospital, Rawalpindi, Pakistan, from January 2024 to January 2025. Neonates with ARM were consecutively enrolled and categorized into early (<48 h of birth) and delayed (>48 h) diagnosis groups. Demographic characteristics, presenting features, postoperative complications following first-stage surgery, and reasons for delayed diagnosis were recorded. All patients underwent a standardized three-stage surgical protocol. Data were analyzed using SPSS v26.0. Continuous variables were compared using Student’s t-test and categorical variables using Chi-square or Fisher’s exact test. A p-value ≤0.05 was considered statistically significant. Results: A total of 82 neonates were included (41 per group). The mean age at presentation was significantly lower in the early diagnosis group (13 ± 8 h) compared with the delayed group (87 ± 25 h; p < 0.01). Abdominal distension (70.7% vs 26.8%; p < 0.01), vomiting (53.6% vs 22.0%; p < 0.01), and sepsis at admission (26.8% vs 4.8%; p = 0.013) were significantly more frequent among delayed cases. Urinary fistula and dehydration did not differ significantly between groups. Postoperative complications and early mortality were numerically higher in delayed cases but did not reach statistical significance. The most common reasons for delayed diagnosis were home delivery without a trained birth attendant, delayed referral from peripheral facilities, misdiagnosis, and absence of routine neonatal examination. Conclusion: Delayed diagnosis of ARM is associated with significantly worse clinical presentation, particularly higher rates of abdominal distension, vomiting, and sepsis at admission. Strengthening routine neonatal examination, improving early referral pathways, and promoting institutional deliveries may reduce diagnostic delays and improve early clinical outcomes in resource-limited settings.